2001
DOI: 10.1016/s0895-7061(01)01305-x
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria as a marker of preclinical diastolic dysfunction in never-treated essential hypertensives

Abstract: Using 24-h ambulatory blood pressure (BP) monitoring and digitized M-mode echocardiography, we evaluated whether microalbuminuria is related to preclinical left ventricular (LV) diastolic dysfunction in hypertensive patients. We selected 87 never-treated hypertensive patients (mean 24-h BP > 140 and/or > 90 mm Hg); albuminuria was evaluated as mean value of 24-h urinary albumin excretion (UAE) from two 24-h urine collections. Microalbuminuria was found in 28 patients, classified as MA+ (UAE 30 to 300 mg/24 h);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
4
0
3
Order By: Relevance
“…Microalbuminuria was defined as that urine albumin-creatinine ratio (ACR) is between 30 μg /mg and 300 μg/mg [ 19 ]. Urine albumin concentration was measured by immunoturbidimetric method [ 20 ]. In addition, fasting blood glucose level, creatinine level and fasting serum lipid status including total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglyceride, and high-sensitive C-reactive protein levels were also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Microalbuminuria was defined as that urine albumin-creatinine ratio (ACR) is between 30 μg /mg and 300 μg/mg [ 19 ]. Urine albumin concentration was measured by immunoturbidimetric method [ 20 ]. In addition, fasting blood glucose level, creatinine level and fasting serum lipid status including total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglyceride, and high-sensitive C-reactive protein levels were also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, the presence of ≥3 cardiovascular comorbidities nearly doubled the risk of MA, while patients with LVH had the highest prevalence of MA (68%). Additionally, Tsioufis et al [27 ]have demonstrated an association between MA and unfavorable cardiac geometric adaptations in essential hypertensive subjects.Furthermore, MA has been shown to be a marker of preclinical diastolic dysfunction in never-treated essential hypertensives [28]. Likewise, it has also been shown than LVH is highly prevalent in hypertensive patients with CKD stages 2-5.…”
Section: Hypertension As a Risk Factor For Subclinical Renal Damagementioning
confidence: 99%
“…A meta-analysis of these studies showed that the presence of MA doubled the risk of CV morbidity or mortality. 3 Besides its role in diabetic nephropathy, MA is also associated with essential hypertension, 4 ischemic heart disease, 5 atherosclerosis, 6 acute stroke, 7 and diastolic dysfunction 8 and is an independent powerful risk factor for fatal and nonfatal vascular events and all-cause mortality in subjects without diabetes. 9,10 In fact, Ibsen et al 11 showed that a reduction in urinary albumin excretion was associated with a reduction in CV events in hypertensive patients treated with blockade of the renin-angiotensin system (RAS).…”
Section: Introductionmentioning
confidence: 99%